Prevalence, incidence, predictive factors and prognosis of silent myocardial infarction: A review of the literature - Valensi, Paul; Lorgis, Luc; Cottin, Yves (Archives of cardiovascular diseases, 2011)
The prevalence, incidence, risk factors and prognosis of silent myocardial infarction are less well known than those of silent myocardial ischaemia. The aims of this article are to evaluate the prevalence and incidence of silent myocardial infarction in subjects with or without a history of cardiovascular disease and in diabetic patients, and to identify potential risk factors and estimate prognosis through a review of the literature. A Medline search identified studies that provided data on the prevalence, incidence, potential risk factors and/or prognosis of silent myocardial infarction, among cohorts from the general population and large clinical studies of at-risk patients (with hypertension or a history of cardiovascular disease or diabetes). The search identified 15 studies in subjects from the general population, five in hypertensive patients, six in patients with a history of cardiovascular disease, and 10 in diabetic patients. The prevalence and incidence of silent myocardial infarction appear highly variable depending on the population studied, the patients’ ages, and the method used to detect silent myocardial infarction. In the general population, the prevalence of silent myocardial infarction increased markedly with increasing age (up to>5% in elderly subjects). Hypertension causes only a moderate increase in prevalence, whereas underlying cardiovascular diseases and diabetes are associated with marked increases in prevalence. The incidence of silent myocardial infarction changes in the same way. The main predictive factors of silent myocardial infarction are hypertension, history of cardiovascular diseases and diabetes duration. Silent myocardial infarction is associated with as poor a prognosis as clinical myocardial infarction. The frequency of silent myocardial infarction and the poor prognosis in at-risk patients amply justify its systematic early detection and active management. Comparativement à l’ischémie myocardique silencieuse, la prévalence et l’incidence de l’infarctus du myocarde silencieux (IDMs), ses facteurs de risque et son pronostic sont mal connus. Évaluer la prévalence et l’incidence de l’IDMs chez des sujets avec/sans antécédents cardiovasculaires et chez des diabétiques, identifier ses facteurs de risque et estimer son pronostic, à partir des données de la littérature. La recherche a été effectuée dans Medline pour identifier, parmi les cohortes de sujets de population générale et les grandes études de patients à risque (hypertension, maladies cardio-vasculaires, diabète), celles évaluant la prévalence et l’incidence de l’IDMs, ses facteurs de risque et son pronostic. La recherche a identifié 15 études en population générale, cinq chez des patients hypertendus, six chez des patients avec antécédents cardiovasculaires et dix chez des patients diabétiques. La prévalence et l’incidence de l’IDMs apparaissent très variables selon la population étudiée, l’âge des patients et la méthode de détection. En population générale, la prévalence de l’IDMs augmente nettement avec l’âge (jusqu’à>5 % chez les sujets âgés). L’hypertension augmente modérément la prévalence, tandis que les maladies cardiovasculaires sous-jacentes et le diabète induisent une nette augmentation de la prévalence de l’IDMs. L’incidence de l’IDMs varie parallèlement. Les principaux facteurs pronostiques sont l’hypertension, les maladies cardiovasculaires et la durée du diabète. Enfin, le pronostic de l’IDMs est aussi péjoratif que celui de l’IDMs clinique. La fréquence et le mauvais pronostic de l’IDMs chez les patients à risque justifient son diagnostic systématique précoce et une prise en charge active.